2018
DOI: 10.1177/2472630317731892
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Aqueous Two-Phase System and Spot-Test Platform for the Rapid Detection of Escherichia coli O157:H7 in Milk

Abstract: Foodborne illnesses are a public health concern in the United States and worldwide. Recent outbreaks of Escherichia coli O157:H7 have brought to light the need for improved ways to detect foodborne pathogens and minimize serious outbreaks. Unfortunately, current methods for the detection of foodborne pathogens are time intensive and complex. In this study, we designed a spot immunoassay that uses a UCON-potassium phosphate salt aqueous two-phase system (ATPS) for the preconcentration of O157:H7. This platform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…DNA sample preparation) and enhanced isothermal DNA amplification (by using the thermophilic helicase-dependent amplification method) [37]. A similar approach was carried by the same research group, by applying ATPS to spot immunoassays and detect foodborne illnesses [98]. In this work, an UCON/phosphate salt ATPS was used for the preconcentration of E. coli 0157:H7 cells, improving the detection limit of the spot test within 30 min and allowing the detection without upstream processing or dilution procedures.…”
Section: Immunological and Biochemical Analysismentioning
confidence: 99%
“…DNA sample preparation) and enhanced isothermal DNA amplification (by using the thermophilic helicase-dependent amplification method) [37]. A similar approach was carried by the same research group, by applying ATPS to spot immunoassays and detect foodborne illnesses [98]. In this work, an UCON/phosphate salt ATPS was used for the preconcentration of E. coli 0157:H7 cells, improving the detection limit of the spot test within 30 min and allowing the detection without upstream processing or dilution procedures.…”
Section: Immunological and Biochemical Analysismentioning
confidence: 99%
“…31 Our group has previously shown that a UCON–potassium phosphate salt ATPS concentrates E. coli cells in a milk sample by more than 10 times, improving the LOD on a spot test immunoassay. 32 Spot test assays utilize the sandwich LFA format, but the antibodies are immobilized on a spot on the membrane as opposed to a line. Additionally, modifications to the GN reporter probes have been designed to increase binding of the target pathogens in the detection zone.…”
Section: Detection Of Surface Markersmentioning
confidence: 99%
“…Through the use of conventional polymer-salt and micellar systems, ATPSs combined with existing detection technologies have been shown to enhance sensitivity in detecting various biomarkers, including 10-fold improvements in LFA detection of parasitic biomarkers (Pereira et al, 2015 ) and viruses (Mashayekhi et al, 2010 ). In a similar manner, the ATPS was also shown to improve sensitivity and decrease time-to-detection of a paper-based spot immunoassay (Cheung et al, 2017 ). However, despite the efficacy of these systems, the limited polarity range of these ATPSs can restrict their use (Freire et al, 2012 ), particularly regarding the partitioning of small hydrophilic proteins.…”
Section: Introductionmentioning
confidence: 98%